2023
DOI: 10.3390/nu15051153
|View full text |Cite
|
Sign up to set email alerts
|

Association between Dietary Habits and Pancreatitis among Individuals of European Ancestry: A Two-Sample Mendelian Randomization Study

Abstract: Dietary factors are believed to potentially influence the risk of pancreatitis. Here, we systematically investigated the causal relationships between dietary habits and pancreatitis by using two-sample Mendelian randomization (MR). Large-scale genome-wide association study (GWAS) summary statistics for dietary habits were obtained from the UK Biobank. GWAS data for acute pancreatitis (AP), chronic pancreatitis (CP), alcohol-induced AP (AAP) and alcohol-induced CP (ACP) were from the FinnGen consortium. We perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…Inadequate access to nutritious food may contribute to malnutrition-an established risk factor for pancreatitis. 29 In other diseases, prior studies have also shown an association between poorer dietary choices with residence in "food swamps/deserts." 30, 31 Thus, environmentally-linked dietary patterns can be hypothesized to be associated with high consumption of saturated fats especially in the context of an inflammatory condition like AP.…”
Section: Discussionmentioning
confidence: 99%
“…Inadequate access to nutritious food may contribute to malnutrition-an established risk factor for pancreatitis. 29 In other diseases, prior studies have also shown an association between poorer dietary choices with residence in "food swamps/deserts." 30, 31 Thus, environmentally-linked dietary patterns can be hypothesized to be associated with high consumption of saturated fats especially in the context of an inflammatory condition like AP.…”
Section: Discussionmentioning
confidence: 99%
“…The strength of the IVs was assessed using the F-statistic. , n = sample size, the coefficient of determination (R 2 ) served as a metric to measure the proportion of variation explained by individual SNP, R 2 is calculated using the following formula ( 25 , 26 ): , where EAF denotes the effect allele frequency, β is the estimated genetic effect size of the SNP, n = sample size, and SE signifies the standard error of the genetic effect size. F-statistic below 10 was considered weak IVs, which might cause biased results and would be excluded.…”
Section: Methodsmentioning
confidence: 99%
“…The genetic IVs that showed associations with the risk or severity of MS at a significance level below 5 × 10 −8 were excluded. We also assessed the IVs strength using the F -statistic ( F = β 2 /se 2 ) ( 27 ). We excluded SNPs with an F -statistic below 10, as they were considered weak IVs and could introduce bias into the analysis.…”
Section: Methodsmentioning
confidence: 99%